Importancia de la comunicación familiar en la prevención de embarazos no deseados en adolescentes de los décimos años de educación básica de la unidad educativa Uyumbicho de la provincia Pichincha, cantón Mejía, parroquia Uyumbicho en el año lectivo 2014-2015 - Cuichán Casamen, Patricia Magali (2015)
Teen pregnancy is a current problem that affects society; especially in educational institutions that are the training centers of society’s youth teen pregnancy harms the economic, physical, social and psychological situation of teens. The motive for this research is to understand the main cause of the lack family communication, using multiple methods such as scientific, descriptive, synthetic, analytical and statistical research. The results of the survey found that there is no good daily communication between and children parents regarding sexuality and contraception, due to the parents’ shame, so a strategy guide has been developed designed in order to help, this affects improve communication at home, using motivational techniques that integrate different concepts and learning with parents and children….